2020
DOI: 10.1101/2020.02.12.20022467
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of absolute humidity on transmission rates of the COVID-19 outbreak

Abstract: A novel coronavirus (COVID-19) was identified in Wuhan, Hubei Province, China, in December 2019 and has caused over 40,000 cases worldwide to date. Previous studies have supported an epidemiological hypothesis that cold and dry (low absolute humidity) environments facilitate the survival and spread of droplet-mediated viral diseases, and warm and humid (high absolute humidity) environments see attenuated viral transmission (i.e., influenza). However, the role of absolute humidity in transmission of COVID-19 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
271
4
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 225 publications
(301 citation statements)
references
References 7 publications
23
271
4
3
Order By: Relevance
“…The effects of seasonality on SARS-CoV-2 are difficult to predict without long time series; supporting evidence for the link between climate and COVID-19 has been largely anecdotal and based on spread in different settings and such analyses are subject to confounding. 40,41 Consequently, we have not incorporated climatic factors into our mathematical model. Future research should be directed towards understanding the potential seasonality of COVID-19 and the climatic factors that could affect its transmission dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of seasonality on SARS-CoV-2 are difficult to predict without long time series; supporting evidence for the link between climate and COVID-19 has been largely anecdotal and based on spread in different settings and such analyses are subject to confounding. 40,41 Consequently, we have not incorporated climatic factors into our mathematical model. Future research should be directed towards understanding the potential seasonality of COVID-19 and the climatic factors that could affect its transmission dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence of a faster spreading of diseases in high humidity levels has been reported, 16 namely for the Legionella disease, although this infection is not caused by a virus. Few papers have been written since mid-February on this topic [17][18][19][20] even though the relationship is not perfectly established and more research is required.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…Although we have shown that the apparent fall in incidence of COVID-19 since CNY's day in China is likely to be attributed to the interventions taken, we cannot rule out the possibility that the decrease was caused by varying timings and intensities of various NPIs taken in different areas as well as some other unknown seasonal factors, e.g. temperature and absolute humidity 43,44. Third, our models and findings were based on someassumptions on parameterizations.…”
mentioning
confidence: 92%